Tracking anemia and its determinants from 2015-16 to 2019-21 in India - Gune, Soyra; Christopher, Anita; Scott, Samuel P.; Nguyen, Phuong Hong; Joe, William; Singh, S. K.; Dwivedi, L. K.; Pedgaonkar, Sarang; Puri, Parul; Chauhan, Alka; Yadav, Kapil; Chamois, Sylvie (International Food Policy Research Institute, 2023)
This Data Note provides an update on the prevalence of anemia and its determinants in India at state and districts levels, as well as coverage of a nutrition specific and nutrition sensitive interventions. Data were from the National Family Health Surveys in 2005 06, 2015 2016 and 2019 21. We first report national trends for 8 population groups (Figure 1 below). For each population group, we show anemia prevalence by severity category and at state and district levels using the two latest rounds of data. Lastly, we show recent trends in determinants of anemia and, nutrition and health interventions.